Designing Listening Tasks For English Students - Irwan D, Darwissyah; Indrasari, Nunun (English Education: Jurnal Tadris Bahasa Inggris, 2019)
Listening skill is one of important skills in learning English. Therefore, it is considered as difficult skill for the students. Designing tasks for listening skill is also challenging  for  the  teachers.  This  paper  describes  possible  ways  in  designing listening tasks for the students. The descriptions include definition, the types of tasks, and the possible ways of designing task for listening skills based on the types of listening performance